ORGANIZATION OF THE EDUCATIONAL PROCESS TAKING INTO ACCOUNT THE FUNCTIONAL ASYMMETRY OF THE BRAIN OF STUDENTS AS A FACTOR OF THE DEVELOPMENT OF THINKING CREATIVITY - GULYAMOV Jahangir Rakhmatullaevich , NURBOEV Kuvondik Mirzanovich , MIRZAYEV Abdurazok Umirzokovich , KALANKHODZHAEVA Kamilakhon Botirkhodzhaevna (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The article considers the issue of taking into account the functional asymmetry of the brain in the educational process as one of the factors of development of creative thinking of students and presents the results of experimental work in this direction.